(untitled) (Journal of NELTA, 2018)
English is a foreign language in Bangladesh, and the tertiary students of private universities of different departments come with different vocational needs. General English courses cannot cater to the specific needs of the students of different departments. Moreover, at a tertiary level, English language courses should be designed not only to help students receive good grades, but also cater to their future workplace needs. In these cases, English for Specific Purposes (ESP) is more applicable than General English language courses. On the other hand, teaching ESP courses is more challenging and difficult than teaching General English courses. The article aims to characterize ESP, analysing its need in Bangladesh and identifying teachers’ roles in its teaching. A survey was conducted for data collection in which two different sets of questionnaires were used for teachers and students. Twenty English language teachers and 64 undergrad students from the Department of Civil Engineering from different universities participated in the survey. Results of the survey have been presented with some recommendations for its pedagogic management. Journal of NELTA , Vol. 22, No. 1-2, 2017 December, Page: 76-88